Adolescents developing life skills for managing type 1 diabetes: a qualitative, realistic evaluation of a guided self‐determination‐youth intervention. (3rd April 2014) - Husted, Gitte R.; Esbensen, Bente Appel; Hommel, Eva; Thorsteinsson, Birger; Zoffmann, Vibeke
Abstract: Aim: To explore and illustrate how the Guided Self‐Determination‐Youth method influences the development of life skills in adolescents with type 1 diabetes supported by their parents and healthcare providers. Background: Evidence‐based methods that accomplish constructive cooperation between adolescents with poorly controlled type 1 diabetes, their parents and healthcare providers are needed. We adjusted an adult life skills intervention comprising reflection sheets and advanced communication for use by adolescent‐parent‐professional triads in outpatient visits. Design: A qualitative realistic evaluation design comprising eight context‐mechanism‐outcome configurations directed the analysis of the Guided Self‐Determination‐Youth's influence on adolescent‐parent‐professional triads to evaluate what worked for whom, how and in what circumstances. Thirteen adolescents aged 13–18 years diagnosed with type 1 diabetes for ≥1 year and having poor glycaemic control participated together with 17 parents and eight healthcare providers. Data were collected from December 2009–March 2012 and consisted of digitally recorded outpatient Guide Self‐Determination‐Youth visits collected during the intervention period (11·5–24·5 months) and semi‐structured interviews at 6‐month follow‐up. Findings: Emerging life skills in adolescents were identified as: (1) developing new relatedness with healthcare providers and parents; (2) becoming decision makers in their own lives with diabetes; and (3) growing personally. Reflection sheets combined with healthcare providers' advanced communication were central to promoting mutual problem‐solving. Conclusion: A life skills approach turned outpatient visits into person‐specific visits with improved cooperation patterns in the triads. Combining reflection sheets and advanced communication skills supported adolescents in beginning a process of developing life skills.